Inland fishing by Homo sapiens during early settlement of Wallacea - Boulanger, Clara; Hawkins, Stuart; Shipton, Ceri; Ingicco, Thomas; Sémah, Anne-Marie; Samper Carro, Sofia; O'Connor, Sue (Frontiers in Environmental Archaeology, 2023)
Homo sapiens were adept at fishing in a range of aquatic habitats by the time they left Africa and reached Southeast Asia ca. 73 Kya. In the insular region of Wallacea, humans adapted to a significant maritime environment with sophisticated marine fishing methods and technology by at least 42 Kya. However, despite a growing array of evidence suggesting an early inland terrestrial adaptation on large islands in this tropical region, there was previously no evidence of fishing in inland wetlands habitats on the depauperate islands of Wallacea. Here we present new evidence of both marine and freshwater fishing recovered from different occupation phases from the cave sites and Matja Kuru 2 (ca. 40 Kya to Late Holocene) on the island of Timor (Timor-Leste), located near significant riverine and lake environments respectively. This indicates that humans adapted to a wider range of aquatic habitats over time and space in Wallacea than previously thought and moved freely between inland and coastal habitats. Diversification of fishing strategies likely improved chances